Uncovering four domains of energy management in palm oil production: a sustainable bioenergy production trend - Al-Madani, Mohammed Hammam Mohammed; Fernando, Yudi; Tseng, Ming-Lang; Abideen, Ahmed Zainul (SPRINGER HEIDELBERG, 2022)
This study aims to identify current and future research trends in sustainable bioenergy production. The systematic review is conducted using a social network analysis method. The data were collected from the Web of Science and Scopus database (2010–2021). Out of the 1747 articles reviewed, 100 were found to be relevant for thematic analysis. The results uncovered four domains of palm oil biodiesel production for sustainable energy management: (1) renewable energy, (2) biodiesel, (3) bioenergy, and (4) life cycle assessment. This study has proposed a sustainable bioenergy production framework based on the four main domains. The framework sheds light on the future of sustainable bioenergy production. The findings indicate the potential growth of the research topic, including sustainable bioenergy, palm oil biodiesel, energy management, and carbon emissions reduction. Future research must incorporate the energy management framework to design a sustainable energy management ecosystem strategy. In addition, the industry must comply with the international sustainability standard and sustainable development goals to manage the energy supply chain and consistency of palm oil biodiesel production.